Associations between lifestyle habits and family members’ health literacy in middle-aged adults with metabolic syndrome: a cross-sectional study in Japan - Goto, Eiko; Okada, Hiroko; Ishikawa, Hirono (Frontiers in Public Health, 2025)
BackgroundHealth literacy has gained importance as a factor related to health behaviors and the risk of developing metabolic syndrome (MetS). Although the health literacy of family members may affect lifestyle habits among individuals with MetS, few studies have examined these relationships. We examined the associations between lifestyle habits (dietary habits, exercise, drinking, and smoking) among individuals with MetS and their family members’ health literacy.MethodsWe conducted a cross-sectional observational study at a Japanese machine manufacturing company using a self-administered questionnaire. Participants were recruited by the health insurance society based on the criterion of specific health guidance; and participants’ family members were also included in this study. Participants’ lifestyle habits were assessed on the basis of specific health checkup questionnaires. Health literacy was assessed using the Communicative and Critical Health Literacy scale. We used two binary logistic regression models to examine the associations of participants’ lifestyle habits with the health literacy of participants and their family members.ResultsWe analyzed data for 125 participants with MetS and 125 family members. After adjusting for variables related to sociodemographic factors and occupation and workplace factors, participants’ exercise habits (moderate exercise, walking/equivalent physical activity) were significantly associated with participants’ health literacy (OR = 4.654, p < 0.001 and OR = 2.689, p = 0.001, respectively). After adjusting for variables related to sociodemographic factors, occupation and workplace factors, and participants’ health literacy, participants’ dietary habits (time dinner is eaten) and exercise habits (moderate exercise) were independently associated with family members’ health literacy (OR = 2.485, p = 0.006 and OR = 2.819, p = 0.034, respectively).ConclusionThe findings suggested that health education for individuals with MetS as well as for their family members may be effective in improving dietary and exercise habits among individuals with MetS themselves. Additional intervention studies are needed to examine which educational model focusing on family is most effective in improving lifestyle habits among individuals with MetS.